Magiczne właściwości Schwärmerei. O roli nalewki w Empuzjonie Olgi Tokarczuk - Zielniewicz, Maria (Przestrzenie Teorii, 2025)
The article analyzes Olga Tokarczuk’s novel The Empusium (Empuzjon), applying actionnetwork theory (Bruno Latour) or object-oriented ontology (Graham Harman). The focus is on the Schwärmerei tincture; on the one hand, this appears as an objectprop aiding in the treatment of tuberculosis; on the other, it possesses its own agency. The author examines the reciprocal relationships between this object and its environment, particularly its connections with the different characters. Viewed in the light of the anthropology of religion, the magical and narcotic properties of the tincture serve as an example of experiencing altered states of consciousness. The change in the perception of reality allows for the blurring of boundaries between binary oppositions: transcendent–material, culture-nature, living–dead, human–non-human, which are at the core of anthropocentrism.